The Effect of Professionalism, Evidence‐Based Practice and Clinical Decision‐Making Levels on the Perception of Individualised Care Among Intensive Care Nurses - Ebubekir Kaplan; Özkan Sir; Muhammet Faruk Yiğit; Musa Ekremen (Nursing in Critical Care, 2026)
ABSTRACT Background In intensive care units, where complex patient needs require evidence‐based clinical decision‐making, individualised care is regarded as one of the cornerstones of high‐quality nursing practice. Aim This study aimed to examine the relationships between professional values, attitudes towards evidence‐based nursing, clinical decision‐making and perceptions of individualised care among intensive care nurses. Study Design A cross‐sectional descriptive study design was employed. Methods Data were collected from intensive care nurses using validated instruments assessing professional values, attitudes towards evidence‐based nursing, clinical decision‐making, and perceptions of individualised care. Results Significant positive correlations were found among all study variables ( p < 0.001). Evidence‐based nursing emerged as the strongest predictor of individualised care (β = 0.444, p < 0.001), followed by professional values (β = 0.165, p < 0.001) and clinical decision‐making (β = 0.112, p = 0.020). The final model explained 35.9% of the variance. Nurses with postgraduate education and longer ICU experience demonstrated higher scores across all variables. Conclusions Attitudes towards evidence‐based nursing were strongly associated with perceptions of individualised care among intensive care nurses. Professional values and clinical decision‐making also contributed significantly to this relationship. Relevance to Clinical Practice Strengthening nurses' participation in evidence‐based practice can support the delivery of better individualised care in intensive care settings.